Methanol extract of Ficus platyphylla decreases cerebral ischemia induced injury in mice. (5th October 2021) - Becker, Axel; Helmuth, Martin; Trzeczak, Doris; Chindo, Ben A.
Abstract: Ethnopharmacological Relevance: Extracts of the stem bark of Ficus paltyphylla (FP) are used in the Nigerian traditional medicine to manage psychoses, depression, epilepsy, pain, and inflammation. Our previous studies revealed that the methanol extract of FP ameliorate body core temperature. Aim of the study: A number of pharmacological agents that utilize mechanisms that enhanced neuronal survival and/or neural regeneration have been developed for the treatment of stroke. Hypothermia protects the brain from damage caused by ischemia by attenuating destructive processes such as neuroinflammation, excitotoxicity, blood-brain barrier disruption, apoptosis, and free radical formation following cerebral ischemia. In the present study, we examined the neuroprotective potential of FP on permanent occlusion of the middle cerebral artery (MCAO)-induced ischemia in mice. Material and methods: C57Bl mice were subjected to MCAO. FP was administered 1 h prior to and immediately after surgery. The brains were collected 24 h later and infarct volumes were measured using immune-histochemical staining, DAPI, NeuN, synaptophysin, and NR2B were quantified. Results: Administration of FP prior to MCAO significantly reduced infarct volume, with no effect on infarct volume immediately after MCAO. Higher numbers of cells and neurons were observed in the peri-infarct area in both groups of mice. FP-induced hypothermia protected tissue in the peri-infarct region from synaptophysin reduction. NMDA receptor 2 (NR2B) immunoreactivity is enhanced by MCAO, with no difference observed in both sham-operated and FP-induced hypothermia groups of mice. Conclusions: The data suggest that FP might be useful in the reduction of ischemia-induced infarct volume when administered prior to the initiation of ischemia with no effect observed after ischemia induction. Graphical abstract: Image 1 Highlights: Ficus platyphylla stem bark extract induced hypothermia. In the MCAO model the extract exerted protective action. Administration prior to ischemia reduced the infarct volume. Administration after ischemia yielded in reduced neuron loss.